Hittite Studies in Honor of Harry A. Hoffner Jr. on the Occasion of His 65th Birthday - Hoffner, Harry A.; McMahon, John Gregory, 1953-; Beal, Richard Henry, 1953-; Beckman, Gary M. (Book collections on Project MUSE., 2004)
Annotation